LTCC tapes based on Al2O3–BBSZ glass with improved thermal conductivity. Issue 10 (December 2015) - Induja, I.J.; Abhilash, P.; Arun, S.; Surendran, K.P.; Sebastian, M.T.
Abstract: A novel low temperature co-fired ceramic (LTCC) composition consisting of 40 wt% Al2 O3 –60 wt% BBSZ (35Bi2 O3 :32ZnO:27B2 O3 :6SiO2 ) fireable at 850 °C has been developed. The XRD study of the sintered composite shows the presence of Bi24 Si2 O40 and ZnAl2 O4 secondary phases. The bulk samples sintered at 900 °C has dielectric constant ( ε r ) of 11.3 and loss tangent (tan  δ ) of 0.001 at 1 MHz. Tapes of the composite have been casted on Mylar ® film and the green tape has a surface roughness of 299 nm and tensile strength of 0.1 MPa. Upon sintering the tapes showed an ε r of 10.9, tan  δ of 0.009 and temperature coefficient of dielectric constant ( τ ε ) of 487 ppm/°C at 5 GHz, which are suitable for practical hybrid device applications.